A Chinese vision on Africa : sociogenesis of the field of expertise on Africa in China - (:unkn) unknown (My University, 2019)
This thesis analyzes the evolution of China’s expertise of Africa and the rise of a champ of African studies “with Chinese characteristics” in the 21st century. From a historical perspective, the author investigates the origins and the development of China’s knowledge on Africa, in order to highlight how African studies in China went from being a marginal field of research in the 1950s to become a hot issue in the 2000 along with the development of China-Africa relations. From a sociological perspective, the author also investigates the evolving conditions and motivations of China’s Africa watchers. She shows how they have come to legitimize and diffuse their expertise vis-à-vis the Chinese government and to what extent their increasing professionalization has contributed to the rise of an epistemic community of China’s Africa Watchers. Finally, a study of their intellectual productions reveals that China’s Africa Watchers have been developing in the 21st century new strategies of intellectual interventions, in order to support China’s foreign policy by connecting Africa-China developmental initiatives to a broader “global perspective”, thus offering a realistic alternative to North—South patterns which dominate the liberal governance model. By investigating how knowledge is produced, assimilated and repackaged by the community of Chinese experts on Africa, this study not only explores the content and the characteristics of China’s knowledge of Africa, but it also highlights narrative patterns and the importance of storytelling as a source of power in the construction — or the contestation — of the relations between actors in the international system.
Keywords: African Research